RHETORICAL STYLE OF STUDENT CRITICISM AT DEMONSTRATIONS AGAINST THE KHUP BILL AND REVISION OF THE 2019 KPK LAW: CRITICAL DISCOURSE ANALYSIS - Andi Hartina Tenrirawe; Lukman Lukman; Ikhwan M. Said (International Journal of Social Science, 2022)
This research was motivated by the event of a demonstration against the KHUP Bill and the Revision of the KPK Law which occurred in 2019. Many student banners were found at the action that contained sentences of criticism of the government but were packaged in the form of humor using a rhetorical style. This study aims to dismantle the rhetorical style of students in the Demonstration of Rejection of the KHUP Bill and the Revision of the 2019 KPK Law. This research uses qualitative descriptive research methods with the Norman Fairclough model of Critical Discourse Analysis approach. The data used as an object is in the form of banner images containing criticism sentences from students at the demonstration of the rejection of the Criminal Code Bill and the revision of the KPK Law which was carried out on September 24-26, 2019. The results showed that students used two rhetorical styles, namely the rhetorical style of euphemism and the rhetorical style of dysphemism.